2017
DOI: 10.1080/14397595.2017.1408755
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of plasma presepsin levels in patients with systemic lupus erythematosus

Abstract: Elevated plasma PSEP levels were correlated with disease activity of SLE, suggesting inappropriate monocyte or neutrophil activation in the pathophysiology of SLE exacerbation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
0
8
0
2
Order By: Relevance
“…Special attention should be directed to baseline levels considered in these conditions, because PSP in RA patients are higher than in healthy controls [20]. Conversely, in other autoimmune diseases such a systemic lupus erythematosus (SLE), PSP correlates with the disease activity of SLE [21]. Therefore, the use of PSP as a bacterial infection biomarker cannot be applied to all autoimmune disease but only to those where PSP is not affected itself by the disease activity.…”
Section: Psp In Autoimmune Diseasementioning
confidence: 99%
“…Special attention should be directed to baseline levels considered in these conditions, because PSP in RA patients are higher than in healthy controls [20]. Conversely, in other autoimmune diseases such a systemic lupus erythematosus (SLE), PSP correlates with the disease activity of SLE [21]. Therefore, the use of PSP as a bacterial infection biomarker cannot be applied to all autoimmune disease but only to those where PSP is not affected itself by the disease activity.…”
Section: Psp In Autoimmune Diseasementioning
confidence: 99%
“…It has been reported that when neutrophils and monocytes phagocytose infectious bacteria in blood vessels, CD14 expressed on their cell surface is taken up by the cells, degraded by neutrophil elastase, and released as presepsin into the blood [14] . However, there are reports of high presepsin levels in patients with SLE without infection, and the cause of this has not been clari ed [18,19] . We focused on NETs, which are known to increase in the blood in sepsis and in SLE patients, to elucidate the production mechanism of increased presepsin even in SLE patients who do not have an infection.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, elevated presepsin levels have been reported in patients with systemic lupus erythematosus (SLE) and hemophagocytic syndrome, autoimmune diseases without evidence of infection, causes of which remain unknown [18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…S. Tanimura и соавт. [23] определяли ПСП у 35 больных СКВ (в том числе 13 -с инфекциями различной локализации) и 72 -с иными системными РЗ (РА, васкулиты, синдром Шегрена, системная склеродермия и др., включая 40 больных с инфекциями). Отмечено более высокое содержание ПСП при СКВ, РА и васкулитах по сравнению с другими нозологиями, однако различия были статистически не значимы.…”
Section: пресепсинunclassified